Riboflavin/UVA collagen cross-linking-induced changes in normal and keratoconus corneal stroma. - Sally Hayes; Craig Boote; Christina S Kamma-Lorger; Madhavan S Rajan; Jonathan Harris; Erin Dooley; Nicholas Hawksworth; Jennifer Hiller; Nick J Terill; Farhad Hafezi; Arun K Brahma; Andrew J Quantock; et al. (PLoS ONE)
Purpose To determine the effect of Ultraviolet-A collagen cross-linking with hypo-osmolar and iso-osmolar riboflavin solutions on stromal collagen ultrastructure in normal and keratoconus ex vivo human corneas. Methods Using small-angle X-ray scattering, measurements of collagen D-periodicity, fibril diameter and interfibrillar spacing were made at 1 mm intervals across six normal post-mortem corneas (two above physiological hydration (swollen) and four below (unswollen)) and two post-transplant keratoconus corneal buttons (one swollen; one unswollen), before and after hypo-osmolar cross-linking. The same parameters were measured in three other unswollen normal corneas before and after iso-osmolar cross-linking and in three pairs of swollen normal corneas, in which only the left was cross-linked (with iso-osmolar riboflavin). Results Hypo-osmolar cross-linking resulted in an increase in corneal hydration in all corneas. In the keratoconus corneas and unswollen normal corneas, this was accompanied by an increase in collagen interfibrillar spacing (p<0.001); an increase in fibril diameter was also seen in two out of four unswollen normal corneas and one unswollen keratoconus cornea (p<0.001). Iso-osmolar cross-linking resulted in a decrease in tissue hydration in the swollen normal corneas only. Although there was no consistent treatment-induced change in hydration in the unswollen normal samples, iso-osmolar cross-linking of these corneas did result in a compaction of collagen fibrils and a reduced fibril diameter (p<0.001); these changes were not seen in the swollen normal corneas. Collagen D-periodicity was not affected by either treatment. Conclusion The observed structural changes following Ultraviolet-A cross-linking with hypo-osmolar or iso-osmolar riboflavin solutions are more likely a consequence of treatment-induced changes in tissue hydration rather than cross-linking.